Fatty acid profile analysis of Chlorella vulgaris under salinity and cadmium stress: Feedstock characterization for biodiesel suitability - Ermavitalini, Dini; Husna, Etika Ziadana Al; Rahayu , Anisa Esti; Rahmahana, Ratna Syifa’a; Solekha, Rofiatun; Purnobasuki, Hery; Ni’matuzahroh, Ni’matuzahroh (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Cultivation of microalgae Chlorella vulgaris under salinity and heavy metal stress can affect the type and quantity of fatty acids in its cells. This study aims to analyze the fatty acid profile of microalgae C. vulgaris InaCCM49 cultivated in media containing 0.6 M NaCl and 95 µM CdCl2 based on the suitability of biodiesel raw material standards. The study began with determining the starter time of microalgae C. vulgaris InaCCM49 culture, cultivation in salinity and cadmium stress medium, determining the growth phase of treatment and control, biomass extraction for metabolomics analysis, UPLC-MS/MS, fatty acid classification using LIPID MAPS Structure Database (LMSD), and analysis of biodiesel quality standards based on ASTM D6751 and EN14214 which include cetane number (CN), saponification value (SV), cold filter plugging point (CFFP), degree of unsaturation (DU), iodine value (IV) and long-chain saturated factor (LCSF). The results showed an increase in the degree of monounsaturated fatty acids (MUFA) by 10.7 % and a decrease in polyunsaturated fatty acids (PUFA) by 36.71% which played a role in the stability of biodiesel compared to the control treatment. The results of the analysis of CN, IV, and CFPP were respectively 55.4, 59, and -16.5. This shows that the composition of fatty acids formed in the microalgae extract C. vulgaris InaCCM49 with salinity and cadmium stress treatment (0.6 M NaCl, 95 µM CdCl2) has the potential to be a source of quality biodiesel raw materials.